2022
DOI: 10.3389/fphar.2022.843409
|View full text |Cite
|
Sign up to set email alerts
|

Naoxintong Capsule Alternates Gut Microbiota and Prevents Hyperlipidemia in High-Fat-Diet Fed Rats

Abstract: Background: Naoxintong Capsule (NXT) is a formulated Traditional Chinese Medicine (TCM) widely applied in the treatment of cardiovascular and metabolic diseases, most of which are closely related to hyperlipidemia as a major risk factor. Given the current limited understandings to the role of gut microbiota in the lipid-lowering effect of NXT and other TCM products, this study investigated the regulation of gut microbiota and lipid metabolism by NXT, and their potential relationship.Methods: The chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The relationship between the gut microbiota and metabolic diseases, especially obesity, is one of the main foci of research in recent years. Emerging evidence has clarified that gut microbiota can regulate the lipid metabolism, which is closely associated with dyslipidemia ( 17 , 19 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between the gut microbiota and metabolic diseases, especially obesity, is one of the main foci of research in recent years. Emerging evidence has clarified that gut microbiota can regulate the lipid metabolism, which is closely associated with dyslipidemia ( 17 , 19 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the gut microbiota, dominated by Bacteroidetes and Firmicutes , has been reported to have a critical impact on the development of obesity ( 19 , 34 ). Firmicutes/Bacteroidetes (F/B) ratio is also commonly used to reflect the changes in microbial structure at the phylum level and is used as a marker to measure overweight and obesity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the effectiveness of TCM in reversing the elevated F/ B ratio in animals with a HFD has been experimentally confirmed. It was found that some natural medicine extracts, proprietary Chinese medicines and Chinese herbal formulas reduce F/B ratio by decreasing Firmicutes abundance and increasing Bacteroidetes abundance, such as Guizhi Tang (GZT) (Yuan et al, 2021), Naoxintong Capsule (NXT) (Lu et al, 2022), Huanglian Jiedu Decoction (HLJD) (Jiang et al, 2021), Quyu Huatan Tongmai Prescription (QYHTTM) (Miao et al, 2022), Danggui Shaoyao San (DGSY) (Yu et al, 2021), Laminaria japonica polysaccharide (LJP) (Zhang et al, 2021d), Porphyran-derived oligosaccharides (PYOs) , Ethyl Acetate Extract of Eleutherococcus senticosus (Rupr. & Maxim.)…”
Section: Tcm Remodels the Structure Of Intestinal Flora To Improve Lmdmentioning
confidence: 99%
“…To play its part in treating LMDs, TCM can control the prevalence of bacteria that produce SCFAs and encourage the generation of SCFAs. LC (Zhang et al, 2019), DLT (Sun et al, 2020), NXT (Lu et al, 2022), IPTS (Ba et al, 2022), LJP (Zhang et al, 2021d), LBPs (Gao et al, 2021), Zanthoxylum bungeanum Maxim. [Rutaceae; Zanthoxyli pericarpium] (ZB) (You, 2016), Ginkgo biloba extract (GbE) , Inulin (Bao, 2021;, NFP (Yang et al, 2020), TP (Wang et al, 2018), Bilberry anthocyanins (Nakano et al, 2020) and COSM (Feng et al, 2022) significantly improved serum lipid levels (TC, TG) as well as reducing lipid accumulation, which may be associated with modifying intestinal flora and increasing SCFAs levels.…”
Section: Tcm Modulates the Level Of Scfas To Improve Lmdmentioning
confidence: 99%